EFFECT OF FOLIAR APPLICATION OF SEAWEED EXTRACT, ZING, AND IRON NANOPARTICLES ON ZIZIPHUS MAURITIANA SEEDLING GROWTH - Diekan A. Saeed; Jassim M. khalaf Al-Ecehagy (European Journal of Agricultural and Rural Education, 2023)
This study was carried out in the wooden canopy of the Department of Horticulture and Landscaping - College of Agriculture - University of Kirkuk during the growing season 2022 to study the effect of foliar spraying with seaweed extract at three levels (0,1,2 ml L-1 ) sequentially and zinc nanoparticles at three levels (0, 10.20 mg L-1 ) and nano-iron at three levels (0,20,40 mg L-1 ) sequentially and the interaction between them in the characteristics of vegetative growth and the chemical content of leaves of Sidr seedlings of the local cultivar. The experiment was designed according to the randomized complete block design (RCBD), a factorial experiment that included three levels of seaweed extract, three levels of nano-zinc, three levels of nano-iron, and three repetitions of four seedlings per experimental unit, bringing the number of observations to 180 and the number of treatments in each sector to 60 treatments. The number of seedlings included in the experiment is 180, and the treatments were randomly distributed among the experimental units. It was noticed that spraying with marine extract at a concentration of 2 ml L -1 led to a significant superiority over the comparison treatment in the following characteristics (carbohydrates, nitrogen, phosphorous, potassium, iron). On the comparative treatment in the following characteristics (carbohydrates, nitrogen, phosphorus, potassium, iron). And the results of the interaction between that when spraying 40 mg L-1 of zinc and iron nanoparticles were significantly superior to the comparison treatment in the following characteristics (carbohydrates, nitrogen, phosphorus, potassium, iron).